First Record of Wide-Eyed Flounder (Bothus podas Delaroche, 1809) in Saroz Bay (Northern Aegean Sea, Turkey) - Özgür Cengiz; Şükrü Şenol Paruğ; Bayram Kızılkaya (Turkish Journal of Agriculture: Food Science and Technology)
A single specimen of the wide-eyed flounder (Bothus podas Delaroche, 1809) was caught using the trammel nets by fishermen on 15 May 2017 in İbrice Bight (Saroz Bay). This paper represents the first record of B. podas for Saroz Bay.